Nucleation and Growth of Amino Acid and Peptide Supramolecular Polymers through Liquid–Liquid Phase Separation. (7th November 2019) - Yuan, Chengqian; Levin, Aviad; Chen, Wei; Xing, Ruirui; Zou, Qianli; Herling, Therese W.; Challa, Pavan Kumar; Knowles, Tuomas P. J.; Yan, Xuehai
Abstract: The transition of peptides and proteins from the solution phase into fibrillar structures is a general phenomenon encountered in functional and aberrant biology and is increasingly exploited in soft materials science. However, the fundamental molecular events underpinning the early stages of their assembly and subsequent growth have remained challenging to elucidate. Here, we show that liquid–liquid phase separation into solute‐rich and solute‐poor phases is a fundamental step leading to the nucleation of supramolecular nanofibrils from molecular building blocks, including peptides and even amphiphilic amino acids. The solute‐rich liquid droplets act as nucleation sites, allowing the formation of thermodynamically favorable nanofibrils following Ostwald's step rule. The transition from solution to liquid droplets is entropy driven while the transition from liquid droplets to nanofibrils is mediated by enthalpic interactions and characterized by structural reorganization. These findings shed light on how the nucleation barrier toward the formation of solid phases can be lowered through a kinetic mechanism which proceeds through a metastable liquid phase. Abstract : Trennung in Arm und Reich : Die Bildung supramolekularer Nanofibrillen aus amphiphilen Aminosäuren und kurzen Peptiden folgt einem Keimbildungs‐Verlängerungs‐Mechanismus, der durch Flüssig‐flüssig‐Phasentrennung vermittelt wird. Die anfängliche Bildung von Flüssigkeitströpfchen, die arm und reich an gelöstem Stoff sind, ist entropiegetrieben, während der Übergang von Flüssigkeitströpfchen zu Nanofibrillen durch enthalpische Wechselwirkungen dominiert wird.